Consumer preferences for dairy products: a study in university retail outlets: Consumer preferences for dairy products: a study in university retail outlets - Shilpa Shree, J; Kathiravan, G; Sarathchandra, Ghadevaru (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Growing health consciousness and awareness of healthy nutrition have increased consumer demand for dairy products. The present study was carried out to assess the consumer preference for different dairy products available at University retail outlets in Chennai city. 100 respondents who bought dairy products were chosen using systematic random sampling procedure from each University retail outlet in Chennai city viz., (i) Urban Chennai (Madras Veterinary College, Vepery) and (ii) Rural Chennai (College of Food and Dairy Technology, Koduvalli). A survey method was adopted for the collection of primary data from consumers with the help of well-structured and pre tested interview schedule. Majority of the respondents (76.0%) preferred pasteurized raw milk sold at university retail outlet due to its freshness and quality. Overall, majority of the respondents preferred khoa (86.0%) followed by ghee (80.0%), ice cream (75.0%), flavoured milk (72.5%), paneer (63.0%), butter milk (55.5%) and chocobar (39.0%). Overall, product safety and taste were considered as the most important reason for buying dairy products at university retail outlets. Overall, attitude of staff and shopping environment were the least important reason for buying dairy products at university retail outlets. University outlets were ranked third in consumer preference for source of dairy products after supermarket and specialized outlets. Majority of them were purchasing fluid milk and chocobar occasionally whereas majority of the respondents purchase flavoured milk, butter milk and ice cream daily as they are refreshment products. Hence, whenever the product is available, consumers are ready to take which indirectly indicates that there is always demand for the dairy products of University. This imparts the need to enhance the production of quality and variety dairy products.